MANAJEMEN PENINGKATAN MUTU: EVALUASI RUMUSAN PROGRAM MANAJEMEN BERBASIS SEKOLAH PADA SATUAN PENDIDIKAN (TINJAUAN LITERATUR) - Dikson Silitonga (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2020)
In order to increase and equalize the educational quality in Indonesia, the government implements a new paradigm in running education with the orientation toward the need of each schools and regions, which is known as School Based Management Program. To evaluate its legal basis, phases of formulation and the clarity of content of the School Based Management Programs, the researcher used the qualitative approach by applying Stake's Countenance Evaluation Model with the library' studies as the collecting data techniques. On the antecedent’s phase, the evaluation results show that the conduction of School Based Management Programs is merely based on the empirical reasons with no clear legal bases hierarchically, a proper formulation as well as having a clarity of content.